Dynamics of proinflammatory cytokine expression in the joints of mice with collagen-induced arthritis (CIA). - Marinova-Mutafchieva, L; Williams, R; Mason, L; Mauri, C; Feldmann, M; Maini, R (1997)
This report contains a description of the cellular localization and kinetics of proinflammatory cytokine expression in murine CIA, a model for rheumatoid arthritis. Tissue cryostat sections of undecalcified paws from type II collagen-immunized DBA/1 mice, taken 1-10 days after the onset of clinical arthritis, were examined for the presence of tumour necrosis factor-alpha (TNF-alpha), IL-1beta and IL-6 using an indirect immunoperoxidase technique. In parallel, interferon-gamma (IFN-gamma) production by lymph node cells, stimulated in vitro with type II collagen, was assessed as a marker of T cell activity. The main areas of TNF-alpha, IL-1beta and IL-6 expression were in the synovial lining layer and in tissue contiguous with cartilage and bone (the marginal zone), in particular at sites of pannus formation and joint erosion. There was a progressive increase in the number of TNF-alpha-, IL-1beta- and IL-6-positive cells from day 1 to day 10 of arthritis, during which time IFN-gamma production by CD4+ T cells from draining lymph nodes declined sharply. A further finding of potential significance was that TNF-alpha was consistently detected at day 1 of arthritis, whereas IL- 1beta-positive cells were not found until day 3, suggesting that the expression of TNF-alpha precedes that of IL-1beta.